Imposition of Added Tax Value on Notary Services/PPAT - Andi Hikmawanti; Jawade Hafidz (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
With the imposition of Added Tax Value (ATV) on notary / PPAT services, it is necessary to know the implementation of the imposition of Added Tax Value on Notaries / PPAT based on the Added Tax Value law and what problems and solutions are faced in charging ATV for such notary / PPAT services. This research is descriptive analytical with an empirical juridical approach with the research location in the Kendari City area. Based on the research results, it was found that the Notary / PPAT in Kendari City has not been registered as a Taxable Entrepreneur in Kendari City. This is due to several reasons, namely the tax office still has difficulty calculating the value of the deed made by the Notary / PPAT in Kendari City because no reporting. Another problem that hinders the collection of ATV for Notaries / PPATs is the demand for collection wages as the government gives incentives to agencies that collect taxes so that they are willing to establish themselves as taxable entrepreneurs.